Approaches and challenges in SARS-CoV-2 vaccine development (2020)
The explosive spread of SARS-CoV-2 suggests that a vaccine will be required to end this global pandemic. Progress in SARS-CoV-2 vaccine development to date has been faster than for any other pathogen in history. Multiple SARS-CoV-2 vaccine candidates have been evaluated in preclinical models and are currently in clinical trials. In this Perspective, we discuss three topics that are critical for SARS-CoV-2 vaccine development: antigen selection and engineering, preclinical challenge studies in non-human primate models, and immune correlates of protection.